Beyond the Lens: Kemi Adetibas King of Boys as A Metaphor for Power and Order in Democratic Nigeria - Onifade, Oluwafemi Sunday (The Journal of Society and Media, 2020)
This study examines the symbolic representations of Nigerian social reality in the movie œKing of Boys. Social reality in this instance is examined from the perspective of official and unofficial political and economic power, influence, and coercion. Based on the framework of Ferdinand de Saussure and Charles Sanders Peirces semiotics and semiology theory, the study aims to examines the symbolic relationship between characters, scenes, and institutions in the Kemi Adetibas œKing of Boys and the realities in the Nigerian political and security sectors. Using the methodological approach of Critical Discourse Analysis, the study found that the movie is a bold attempt at representing the intricate power relations that exists within Nigerian political circles as well as that which exists between the Nigerian political class and organized crime